Aerothermal effect of cavity welding beads on a transonic squealer tip - Vieira, J; Coull, J; Ireland, P; Romero, E (American Society of Mechanical Engineers, 2021)
High-pressure turbine blade tips are critical for gas turbine performance and are sensitive to small geometric variations. For this reason, it is increasingly important for experiments and simulations to consider real geometry features. One commonly absent detail is the presence of welding beads on the cavity of the blade tip, which are an inherent by-product of the blade manufacturing process. This paper therefore investigates how such welds affect the Nusselt number, film cooling effectiveness and aerodynamic performance.